2020
DOI: 10.19184/geosi.v5i2.17873
|View full text |Cite
|
Sign up to set email alerts
|

Soil Zonation and The Shaking Table Test of The Embankment on Clayey Soil

Abstract: The main objective of this research was to model the zonation of wrap faced embankment on soft clay foundation, by applying a shake table test. Also, to investigate the dynamic behaviors of clay soil, such as acceleration amplification, displacement and pore water pressure of wrap faced embankment. This was done with respect to changes in frequencies of 1 Hz, 3 Hz, 5 Hz, 10 Hz, 12 Hz and 15 Hz respectively. Constant acceleration (0.1 g) and surcharge (19 Kg) were applied by using a laminar box, placed on a sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Previous studies have investigated soft clay soil issues in agricultural areas. For instance, Hore et al (2020) has successfully created a model for zonation of soft clay soil. Nasir et al (2019) has reported the rubber wheel tractors and half-track tractors can devastate the soil hardpan layer and may cause soft soil spots around the paddy fields.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated soft clay soil issues in agricultural areas. For instance, Hore et al (2020) has successfully created a model for zonation of soft clay soil. Nasir et al (2019) has reported the rubber wheel tractors and half-track tractors can devastate the soil hardpan layer and may cause soft soil spots around the paddy fields.…”
Section: Introductionmentioning
confidence: 99%
“…Soil quality analysis based on remote sensing is needed to assess land variability (Reddy et al, 2020). Meanwhile, remote sensing technology is commonly used to classify land, based on several criteria with high accuracy (Hore et al, 2020).…”
Section: Introductionmentioning
confidence: 99%